Statin-induced changes in mitochondrial respiration in blood platelets in rats and human with dyslipidemia - Vevera, J; Fišar, Z; Nekovářová, T; Vrablík, M; Zlatohlávek, L; Hroudová, J; Singh, N; Raboch, J; Valeš, K (Physiological research, 2016)
3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase inhibitors (statins) are widely used drugs for lowering blood lipid levels and preventing cardiovascular diseases. However, statins can have serious adverse effects, which may be related to development of mitochondrial dysfunctions. The aim of study was to demonstrate the in vivo effect of high and therapeutic doses of statins on mitochondrial respiration in blood platelets. Model approach was used in the study. Simvastatin was administered to rats at a high dose for 4 weeks. Humans were treated with therapeutic doses of rosuvastatin or atorvastatin for 6 weeks. Platelet mitochondrial respiration was measured using high-resolution respirometry. In rats, a significantly lower physiological respiratory rate was found in intact platelets of simvastatin-treated rats compared to controls. In humans, no significant changes in mitochondrial respiration were detected in intact platelets; however, decreased complex I-linked respiration was observed after statin treatment in permeabilized platelets. We propose that the small in vivo effect of statins on platelet energy metabolism can be attributed to drug effects on complex I of the electron transport system. Both intact and permeabilized platelets can be used as a readily available biological model to study changes in cellular energy metabolism in patients treated with statins.
Keywords: Mitochondria; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Rats; statiny; dyslipidemie; trombocyty; Blood Platelets; Animals; Dyslipidemias; Humans; krysa rodu Rattus; lidé; mitochondrie; buněčné dýchání; zvířata; Cell Respiration